2001
DOI: 10.1002/ijc.10112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high‐risk human papilloma virus types and its association with P53 codon 72 polymorphism in tobacco addicted oral squamous cell carcinoma (oscc) patients of Eastern India

Abstract: Key words: p53 polymorphism; HPV; oral cancerOral squamous cell carcinoma (OSCC) is the sixth most common malignancy and is a major cause of cancer morbidity and mortality worldwide. The overall survival percentage has not changed in recent years, despite extensive research on the biological and molecular aspects of oral SCC. Among the more pressing problems in clinical management are the lack of early detection and the high incidence of local-regional recurrence, even with aggressive surgical therapy. OSCC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 27 publications
13
97
2
4
Order By: Relevance
“…They have observed that the Proline allele was more frequent in control population and no association was found between oral cancer risk and Arg72Pro polymorphism. Another study from east region of India noted that Arginine allele was more frequent in population (Nagpal et al, 2002). In the present study, Arginine allele was more frequent in this population.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…They have observed that the Proline allele was more frequent in control population and no association was found between oral cancer risk and Arg72Pro polymorphism. Another study from east region of India noted that Arginine allele was more frequent in population (Nagpal et al, 2002). In the present study, Arginine allele was more frequent in this population.…”
Section: Discussionsupporting
confidence: 62%
“…The controls as well as the cases belonged to same ethnicity and were from the same geographic location. An allele frequency of Arg72Pro polymorphism has been reported to vary with respect to ethnicity and latitude (Nagpal et al, 2002). The allele frequency of proline at codon 72 varies from 0.12-0.69 worldwide (Francisco et al, 2011) whereas for the Indian population; it ranges from 0.42-0.72 (Nagpal et al, 2002;Tandle et al, 2001;Mitra et al, 2003;Mittal et al, 2011;Suresh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The reported HPV prevalence in oral cancers in India varied from 0 to 100% in studies using biopsies in cases and PCR assay for HPV detection and genotyping. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the studies using a methodology similar to ours (oral brushing to collect epithelial cells instead of biopsy, combined with PCR for detection and genotyping), the prevalence reported for oral cancer cases was 31.5 26 and 32.4%. 15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested).…”
Section: Discussionmentioning
confidence: 99%
“…12 One-on-one semistructured interviews using a questionnaire and life grid technique, which has been shown to improve recall, 13 were conducted by three professionally trained dentists. Data collected included sociodemographic information, religious beliefs, environmental variables and sexual behavior including age at first sexual intercourse, number of sexual partners and oral sex practice frequency during three different life stages ( 16,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and >30 years).…”
Section: Patient and Data Collectionmentioning
confidence: 99%
“…Although recent advancement in research methodologies as well as longitudinal follow up of the rate of incidence, confirms genetic factors as a major contributing factor in etiopathogenesis of such malignancies [3][4][5].…”
Section: Introductionmentioning
confidence: 99%